PENGARUH FAMILY FINANCIAL SOCIALIZATION, INCOME, SELF-CONTROL, DAN FINANCIAL ATTITUDE TERHADAP SAVING BEHAVIOR GENERASI SANDWICH DI KOTA SURABAYA - Luthfiannisa, Galuh; Meidiaswati, Harlina (Universitas Negeri Surabaya, 2024)
This study examines the influence of Family Financial Socialization, Income, Self-control, and Financial Attitude on Saving Behavior of the Sandwich Generation in Surabaya. The data collection technique was carried out using purposive sampling with a total of 200 respondents. Questionnaires were distributed online and offline to minimize misinterpretation from respondents. The results showed that the variables of Family Financial Socialization, Income, Self-control, and Financial Attitude had a positive effect on Saving Behavior of the Sandwich Generation in Surabaya. This is because, good financial socialization from parents can shape positive financial attitudes and behaviors, including saving behavior. In addition, the higher a person's income level, the higher the level of consumption and savings, due to the lack of barriers compared to low-income people. A person with good self-control will be able to avoid consumptive behavior, delay desires, determine a priority scale and focus on long-term financial goals. Financial Attitude has a positive effect on saving behavior because good financial attitudes reflect the ability to manage risk and mature financial planning.